Epicardial and Perihepatic Fat as Cardiometabolic Risk Predictors in Girls with Turner Syndrome: A Cardiac Magnetic Resonance Study - Nanees A. Salem; Nihal M. Batouty; Ahmed M. Tawfik; Donia M. Sobh; Basma Gadelhak; Shimaa R. Hendawy; Wafaa Laimon (Galenos Yayincilik, 2021)
Objective:Turner syndrome (TS) patients are at high risk of cardiometabolic disorders. Cardiometabolic risk factors are more commonly related to visceral rather than total body adiposity. Adipocytokines have been explored as a potential link between obesity and obesity-related cardiometabolic dysfunction. This study explored the validity of epicardial fat-thickness (EFT) and perihepatic fat-thickness (PHFT) measurement as cardiometabolic-risk predictors in TS-girls in relation to standard obesity-indices and metabolic syndrome (MetS) components.Methods:Forty-six TS girls and twenty-five controls (10-16 years) were subdivided into two age-groups (10 to less than 13 and 13-16). Participants were assessed for body mass index (BMI) Z-scores, waist circumference (WC), total-fat mass (FM) and trunk-FM by bioimpedance-technique, EFT and PHFT by cardiovascular magnetic resonance, lipid-profile, homeostasis model assessment of insulin resistance (HOMA-IR), and serum chemerin. MetS was defined according to International Diabetes Federation criteria.Results:Overweight/obesity and MetS were detected in 45.7% and 37% of TS-girls respectively. BMI Z-score, WC, total-FM, trunk-FM, EFT and PHFT values were significantly higher in TS-age groups compared to age-matched control groups, being more pronounced in the older group when TS-girls had been exposed to estrogen. Dyslipidemia, higher HOMA-IR, chemerin, EFT and PHFT values were observed in lean-Turner compared to BMI-Z-matched controls. EFT and PHFT were significantly correlated with chemerin and several components of MetS. EFT at a cut-off-value of 6.20 mm (area under the curve=0.814) can predict MetS in TS-girls.Conclusion:TS-girls displayed an adverse cardiometabolic profile during late childhood and adolescence. EFT and PHFT are emerging cardiometabolic risk predictors in TS-patients. Excess EFT rather than total body adiposity may contribute to altered metabolic profile among lean-Turner patients.